Detection of Genetic Modified Feed Component - H. Younis, Mohammed; Q. Younan, Hayba; H. Khudhair, Saad; L. Aarif, Ghaith; R. Abdulha, Heba (Iraqi Journal of Science, 2023)
There are growing concerns over the possibility of transfer genetically modified sequences from genetically modified feed component (GM feed) to animals and their products, moreover, affect these sequences on animal and human health. This study was implemented to detect P35S in modified feed by using PCR technique by detecting presence P35S promoter, which responsible for the regulation of gene expression for most of the transgenic genes. Thirty eight feed samples were collected from different sources of Baghdad markets, which have been used for feeding livestock, comprise 21 coarse mixes feed, 13 pelleted feed, and 4 expanded feed. Genomic DNA was extracted by using two methods, CTAB method and Wizard kit. In order to verify the presence (P35S) in feed samples, a pair of primer for 35S promoter was used. The results of the present study showed that 58% of tested samples contained promoter P35S this means presence genetically modified feed in the Baghdad market.